DASAR PENGEMBANGAN MEDIA SAILBOATS A TRACK MODEL PEMBELAJARAN STEM UNTUK KELOMPOK B SUB TEMA BENDA-BENDA ALAM - Mau'izhah, Firda Ruhyah; Rahman, Taopik; Mulyana, Edi Hendri (JURNAL PAUD AGAPEDIA, 2021)
This research is based on the actual condition in the field that there are still limited learning media based on Science, Technology, Engineering, and Mathematics (STEM) for the sub-theme of natural objects at the early childhood education level. The learning media are partial or only focussed on one scientific subject. Teacher posses limited knowledge about STEM learning model, therefore the media created has not been able to optimize all STEM learning components. Moreover, there are material that is difficult to explain, such as the sub-themes of natural objects. Considering this background, researcher conduct this study in order to develop a product in the form of STEM-based learning media for group B sub-theme of natural objects. This study used a mixed research approach with research design development and research methods Educational Design Research (EDR) McKenney Thomas C Reeves model. The results of this study indicate that the basic need of this study was the development of STEM learning model media for group B sub-theme of natural objects.Penelitian ini didasari oleh fakta yang terjadi di lapangan bahwa masih terbatasnya media pembelajaran berbasis Science, Technology, Engineering, dan Mathematics (STEM) untuk sub tema benda-benda alam pada jenjang pendidikan anak usia dini. Media pembelajaran yang digunakan masih bersifat parsial atau hanya terfokus pada satu bidang keilmuan saja, pengetahuan guru mengenai model pembelajaran STEM juga masih minim sehingga media yang dibuat belum bisa mengoptimalkan seluruh komponen pembelajaran STEM, selain itu terdapat materi yang sukar dijelaskan yakni pada sub tema benda-benda alam. Berdasarkan hal tersebut, penelitian ini dilakukan untuk mengembangkan produk berupa media pembelajaran berbasis STEM bagi kelompok B sub tema benda-benda alam. Peneletian ini menggunakan pendekatan penelitian campuran (mix method) dengan desain penelitian pengembangan dan metode penelitian Educational Design Research (EDR) model McKenney Thomas C Reeves. Hasil penelitian menunjukkan bahwa kebutuhan dasar dari penelitian ini adalah perlunya pengembangan media model pembelajaran STEM untuk kelompok B sub tema benda-benda alam.